EFEKTIVITAS DAYA HAMBAT EKSTRAK DAUN UBI JALAR UNGU (Ipomoea batatas) TERHADAP BAKTERI Aeromonas hydrophila PADA IKAN NILA (Oreochromis niloticus) - Nur Fajriani Nursida; Nursidi Nursidi; Indrayani Indrayani; Arman Pariakan (Faculty of Science and Technology University Ibrahimy, 2025)
The primary challenge encountered in the production of tilapia is a bacterial disease that is induced by the bacterium Aeromonas hydrophila. Crop failure and the mortality of cultured animals are among the consequences. Certain herbal plants contain antioxidants that can exert a therapeutic effect against the A. hydrophila bacterium. The objective of this investigation is to ascertain the survival of fish following infection with A. hydrophila bacteria and their behavior and morphology prior to and following immersion in purple sweet potato leaf extract (Ipomoea batatas). In the initial stage, the survival rate was assessed through the challenge test with A. hydrophila 108 bacteria. The second stage involved the observation of the behavior and morphology before and after immersion in purple sweet potato leaf extract (I. batatas). This research was conducted in two phases. The treatment concentrations were as follows: treatment A (without extract / 0 mg/L), treatment B (40 mg/L), treatment C (60 mg/L), and treatment D (80 mg/L). In the research, abnormal behavioral changes, including the presence of red sores on the tail and a decline of appetite, were observed. The fish maintained an appetite, exhibited normal body movements, and swam actively when treated with D. Conversely, treatment A demonstrated a subpar response until the conclusion of the observation period. The effective inhibition of mortality in Nile tilapia was demonstrated by the survival rate of Nile tilapia larvae infected with A. hydrophila bacteria after treatment with a solution of purple sweet potato leaf extract (I. batatas) for 24 hours. The survival rate was observed over a 7-day period.